Carbonized Tree‐Like Furry Magnolia Fruit‐Based Evaporator Replicating the Feat of Plant Transpiration (Global Challenges 10/2019). Issue 10 (4th October 2019) - Bian, Yue; Shen, Yang; Tang, Kun; Du, Qianqian; Hao, Licai; Liu, Dongyang; Hao, Jinggang; Zhou, Dong; Wang, Xiaokun; Zhang, Huiling; Li, Peiye; Sang, Yimeng; et al.
Abstract : In article number1900040, Kun Tang, Xiang Xiong, Shulin Gu, and co‐workers utilize carbonized magnolia fruits as energy‐harvesting vapor generators. The hidden talent of the magnolia fruit lies in its tree‐like structure in both macro‐ and micro‐scales. This work could inspire more biomimetic evaporator designs in the aim to tackle freshwater scarcity in a green and sustainable way.